Lesbian Gay Biseksual and Transeksual (LGBT) polemic in Indonesia: a study of the opinion of the Indonesian Ulama Council and the Liberal Islam Network (JIL) - Usman, Munadi (Penerbit Universiti Kebangsaan Malaysia, 2018)
The LGBT issue re-emerged in Indonesia and has become a warm polemic in society, this issue has split the community into two groups, the supportive and the rejecting groups. Each side expressed their views on this issue with different reasons and approaches. The two most distinct groups of differing views on this issue are the Indonesian Ulama Council and the Liberal Islam Network. This study examines the evolutionary thinking dynamics among LGBT Indonesian Muslim scholars, with the aim of understanding the basis, approach and reasons used by each in determining opinions about LGBT behavior. The approach used in this study is descriptive comparative, namely the type of research used to compare between two groups or more than a certain variable. As for the conclusion of this study that MUI strongly opposes LGBT behavior under the pretext of contradicting the Qoran-Hadis and human nature created in pairs. While JIL groups support LGBT under the pretext of sexual preference and human rights.